2001
DOI: 10.1021/ed078p1107.6
|View full text |Cite
|
Sign up to set email alerts
|

Novak's Theory of Education: Human Constructivism and Meaningful Learning

Abstract: P r i n t • S o f t w a r e • O n l i n e • B o o k s J o u r n a l o f C h e m i c a l E d u c a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
239
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(253 citation statements)
references
References 17 publications
5
239
0
9
Order By: Relevance
“…What students learn must be connected to what they already know and what they are going to learn Another evidence-supported approach is that of meaningful learning [13,14]. Meaningful learning acknowledges that students construct knowledge, but it also recognizes that this knowledge construction must be build on a firm foundation, and must lead somewhere meaningful (to the student).…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 99%
“…What students learn must be connected to what they already know and what they are going to learn Another evidence-supported approach is that of meaningful learning [13,14]. Meaningful learning acknowledges that students construct knowledge, but it also recognizes that this knowledge construction must be build on a firm foundation, and must lead somewhere meaningful (to the student).…”
Section: Evidence-based Approaches To Teaching and Learningmentioning
confidence: 99%
“…These issues have been extensively discussed in publications of the Towns Research Group (Purdue University Department of Chemistry) and Bretz Research Group (Miami University). Numerous works have been devoted to the study of chemical laboratory course framed by Ausubel's assimilation theory of cognitive learning (Novak 1993(Novak , 2010 and meaningful learning (Bretz 2001). These studies revealed inconsistency between faculty goals, student expectations and learning outcomes across three domains of meaningful learning: affective (attitudes and emotions), psychomotor (physical skills) and cognitive (content knowledge growth) (Brandriet, Ward and Bretz 2013;Bruck, Towns and Bretz 2010;DeKorver and Towns 2016;Bretz 2015a, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In order to measure students' perceptions of their learning in the university chemistry laboratory, we developed the Meaningful Learning in the Laboratory Instrument (MLLI) (Galloway and Bretz, 2015) using Joseph Novak's Theory of Meaningful Learning and Human Constructivism (Novak, 1993(Novak, , 2010Bretz, 2001). A meaningful learning experience ''underlies the constructive integration of thinking, feeling, and acting leading to human empowerment for commitment and responsibility'' (Novak, 2010, p. 18).…”
Section: Introductionmentioning
confidence: 99%